Jasmineira filatovae Levenstein, 1961, the deepest known sabellid is a Potamethus Chamberlin, 1919: redescription, new combination and generic emendation - Tovar-Hernandez, Maria Ana; Jirkov, Igor A. (Zootaxa, 2024)
Jasmineira filatovae Levenstein, 1961 was described from the Bering Sea from sediments at 3812–3940 m. Later, it was reported from 6328–9735 m in the Aleutian and Japan Trenches, thus becoming the deepest sabellid ever recorded. In the present study, syntypes of J. filatovae were examined. The syntypes possess anterior and posterior peristomial rings distinctly elongated, ventral sacs, parallel lamellae, companion chaetae and avicular thoracic uncini with long handles, and lack bayonet chaetae and inter-radiolar membrane. This combination of features does not match the diagnosis of Jasmineira Langerhans, 1880, but does match that of Potamethus Chamberlin, 1919. Consequently, the new combination of Potamethus filatovae (Levenstein, 1961) is presented with a complete redescription; further, a lectotype is proposed and other specimens are regarded as paralectotypes. Specimens of P. malmgreni (Hansen, 1887) were examined form the Norwegian Sea and the Arctic Ocean for comparative purposes. The diagnosis of the genus Potamethus is emended based on the variability found in some species: 1) the inter-radiolar membrane may be present, 2) peristomial moldures present in some species, 2) thoracic uncini with long handles, and 3) a hump on the angle between external margin of neck and handle of thoracic and abdominal uncini may be present.